Kelimpahan Limnodrilus sp. pada Perairan Kanal di Kecamatan Pontianak Timur - Ari Hepi Yanti, Arfan Setiawan, Tri Rima Setyawati (Universitas Tanjungpura, 2015)
The canals for the people in Subdistrict of East Pontianak was instrumental to the activity of the residents generally live in the area around the canals flow. Increased development and trading activities made the canals are particularly susceptible to contamination. The purpose of this research is to know the abundance of Limnodrilus sp., as well as canals water quality in terms of abundance Limnodrilus sp. Sampling is done on three canals based on differences in hue the environment around a canal, like in the Village of Tanjung Hulu, Saigon and Dalam Bugis. Based on the result, the abundance of Limnodrilus sp. ranged from 133,33 ind./m2 - 5200 ind./m2. The highest abundances Limnodrilus sp. was found in a canal at the Village of Saigon with a value of 5200 ind./m2. The abundance of Limnodrilus sp. in Subdistrict of East Pontianak include into overflow categories.